Utiliza????o da metodologia da condi????o tra??adora para avalia????o do processo assistencial oferecido aos doentes com sepse grave e choque s??ptico - Pulzi J??nior, S??rgio Ant??nio (2014)
Introduction: The analysis of healthcare quality can be performed by assessing the care process. To this end, a broad concept of quality is necessary, which has three domains: structure, process and outcome. The exclusive assessment of outcome is somewhat interesting to evaluate efficiency and effectiveness. On the other hand, the evaluation of the care process is better to understand how healthcare services are carried out. Finally, the structure analysis allows realize how care is organized. In 1969, the Institute of Medicine expressed that specific diseases could be used as "tracers" to analyze healthcare services. This kind of evaluation could allow understanding the interplay among professionals, patients and the setting. Furthermore, it could provide information easy to understand and it would allow the development of suggestions that could be able to positively change the process of providing healthcare services. Purpose of research: This research aims to analyze the management of the care process using the sepsis as tracer disease of quality. The study was intended to understand whether this analysis would be able to contribute to the improvement of quality in the hospital setting. Results: After the selection of the study sample, the number of eighteen patients of a particular Brazilian public hospital was retrospectively evaluated. It was performed medical record review and the data collection was done in a specific research instrument. The adherence to quality indicators of the care process in sepsis, proposed by the Surviving Sepsis Campaign, was low: measure lactate level = 22%; blood cultures prior to administration of antibiotics = 33%; administer blood spectrum antibiotics = 28%; use of crystalloids or vasopressors = 72%; measurement central venous pressure = zero; measurement central venous oxygen saturation = 6%. Neither case had joint realization of all the items mentioned. Time indicators demonstrated that there was excess length of stay in the emergency department before hospitalization; delay in detection and diagnosis of sepsis; unavailability of beds in intensive care for immediate hospitalization. Furthermore, especially in surgical patients, there was a difficulty assessing specialized human resources and special facilities for diagnosis. Conclusion: The healthcare in sepsis appears to be sensitive to the quality of service delivery. This analysis allows the detection of care failures and to propose possible solutions.